A new design of transformerless, non‐isolated, high step‐up DC‐DC converter with hybrid fuzzy logic MPPT controller - Basha, Chakarajamula Hussaian; Murali, Matcha (International journal of circuit theory and applications, 2022)
Under Partial Shading Conditions (PSCs), the solar PV nonlinear characteristics consist of multiple Maximum Power Points (MPPs). As a result, it is very difficult to extract the peak power of the solar PV. In this article, an Improved Grey Wolf Optimization‐based Fuzzy Logic Controller (IGWO‐FLC) is proposed to track the MPP of the solar PV. The advantages of the proposed hybrid soft computing Maximum Power Point Tracking (MPPT) controller are high accuracy, very less oscillations across MPP, and high tracking speed. Also, a new transformerless, high step‐up, Non‐isolated Boost Converter (NIBC) is introduced in this work to improve the voltage profile of the solar PV system at different atmospheric conditions. The introduced converter circuit makes use of the network LC3D3 to improve the voltage conversion ratio, reduced voltage stress on switches, and universal input voltage. In addition, the network LC3D3 acts as a filter to reduce the output power ripples of the converter. The steady‐state performance of the proposed converter is analyzed at Continuous Conduction Mode (CCM) and Discontinuous Conduction Mode (DCM) of operations. The MATLAB/Simulink window is used to validate the proposed PV fed NIBC system at uniform and different PSCs of the solar PV. Also, the NIBC performance is investigated by applying an M62252P8020 type programmable DC‐source. An Improved Grey Wolf Optimization‐based Fuzzy Logic Controller (IGWO‐FLC) is used in this article to track the MPP of the solar PV. The advantages of the proposed hybrid soft computing Maximum Power Point Tracking (MPPT) controller are high accuracy, very less oscillations across MPP, and high tracking speed. Also, a new transformerless, high step‐up, Non‐isolated Boost Converter (NIBC) is proposed in this work to step‐up the PV system output voltage at different atmospheric conditions. The proposed converter circuit makes use of the network LC3D3 to improve the voltage conversion ratio, reduced voltage stress on switches, and universal input voltage.